Copper and nickel doped carbon dots for rapid and sensitive fluorescent turn-off detection of bilirubin - A. Lakshmi Devi; M. Sreelakshmi; P. V. Suneesh; T. G. Satheesh Babu (Scientific Reports)
Abstract Carbon dots doped with metals and non-metals have gained much popularity due to the enhancement in their optical and electronic properties. In this study, polyethyleneimine-functionalized transition metal (nickel or copper) doped carbon dots (CD, NiCD and CuCD) were synthesized through hydrothermal method. The carbon dots exhibited a blue fluorescence at 470 nm when excited at 350 nm. The as-synthesized carbon dots were utilised for the fluorimetric detection of bilirubin in the range 0.5 µM – 280 µM, with CuCD exhibiting the highest sensitivity of 155.38 a.u/log µM in the concentration range 0.5 to 10 µM and 84.01 a.u/ log µM in the concentration range 10 to 280 µM. CuCD also exhibited the lowest limit of detection of 0.0907 µM and the lowest limit of quantification of 0.3023 µM. All the carbon dots showed negligible interference in the presence of biomolecules and metal ions present in human serum implying the remarkable selectivity of the method to bilirubin detection. Further, the carbon dots were successfully tested for their real-time application in human serum using bilirubin-spiked serum samples.